Selective Defect Passivation and Topographical Control of 4‐Dimethylaminopyridine at Grain Boundary for Efficient and Stable Planar Perovskite Solar Cells. Issue 10 (27th January 2021) - Song, Seulki; Park, Eun Young; Ma, Boo Soo; Kim, Dong Jun; Park, Helen Hejin; Kim, Young Yun; Shin, Seong Sik; Jeon, Nam Joong; Kim, Taek‐Soo; Seo, Jangwon
Abstract: Recent progress in highly efficient perovskite solar cells (PSCs) has been made by virtue of interfacial engineering on 3D perovskite surfaces for their defect control, however, the structural stability of the modified interface against external stimuli still remains unresolved. Herein, 4‐dimethylaminopyridine (DMAP) is introduced to develop a facile technique for selectively passivating the grain boundary (GB) and controlling the topographical boundary of the perovskite surface near the GB. Through the surface treatment of DMAP, strongly bound DMAP crystals are selectively formed at the GB, which serves two functions: nonradiative recombination at GB is effectively reduced by healing the uncoordinated Pb 2+ while adhesion strength between the perovskite and the poly(triaryl amine) (PTAA) polymer is significantly enhanced by a mechanical interlock effect. A planar PSC with DMAP treatment exhibits a champion power conversion efficiency of 22.4%, which is not only much higher than the 20.04% observed for a nontreated control device, but also the highest among the planar PSCs using PTAA polymers as a hole transport material. Furthermore, the use of DMAP leads to a substantial improvement in the device stability under damp‐heat test and light irradiation. Abstract : 4‐Dimethylaminopyridine (DMAP) is introduced to develop a facile technique for selectively passivating grain boundaries (GB) and controlling the topographical boundary of perovskite surfaces near GBs. A power conversion efficiency of 22.4% is achieved for a planar perovskite solar cell with DMAP treatment and the device stability under damp‐heat and light irradiation is improved.